Giant sigmoid colon diverticulum - Christian Corbin Frye, MD; Matthew Paul Landman, MD, MPH (Elsevier, 2018)
Giant colonic diverticula are uncommon in all age groups and are especially rare within the pediatric population, with only one known previously reported case in a child. In this case presentation, we report a rare case of a pediatric GCD, review relevant epidemiology and histology, and discuss diagnostic and treatment options. The patient was an 11-year old female with worsening chronic constipation, abdominal pain, and vomiting. CT found a large pelvic mass that was removed via sigmoidectomy and found to be a Type 3 (true diverticula) GCD, which make up only 12% of all GCD's. Pediatric GCD's can be mistaken for the much more common enteric duplication cyst, but both pathologies require surgery. Because of the uncommon nature of GCD, the authors recommend CT as the diagnostic modality of choice because of its high sensitivity and ability to aid in preoperative planning. The authors also recommend treating pediatric GCD with segmental colectomy to avoid recurrence and even a remote risk of colonic adenocarcinoma.